Assessment the hydrogen-electric coupled energy storage system based on hydrogen-fueled CAES and power-to-gas-to-power device considering multiple time-scale effect and actual operation constraints. (22nd March 2023) - Zhao, Pan; Xu, Wenpan; Liu, Aijie; Wu, Wenze; Wang, Jiangfeng; Wang, Xiaopo
Abstract: Energy storage technology provides efficient energy management in renewable driven power system. The long duration time-scale fluctuation in unbalance power becomes more obvious and prominent with the elevated renewable penetration level. However, this issue is not widely considered in current energy storage system. In this paper, a green hydrogen-electric coupled energy storage system based on hydrogen-fueled compressed air energy storage (CAES) and power-to-gas-to-power (PtGtP) device is proposed. The hydrogen-based PtGtP device, including proton exchange membrane fuel cell (PEMFC) and PEM electrolzyer, is employed to smooth out the long duration time-scale fluctuation. Whereas, the hydrogen-fueled CAES is used to settle the remaining time-scale fluctuations. Moreover, the coupled feature is reflected by the hydrogen medium. The hydrogen only generates in PtGtP device, but consumes in both PtGtP device and hydrogen-fueled CAES. The performance assessment by considering the actual operation constraints is conducted based on historical data from real world. The simulated results show that the proposed system can provide an effective and flexible power management in the high share renewable power system. The loss of power supply probability (LPSP) is 5.40%, which is higher than that of any single energy storage system. However, the wind curtailment ratio (WCR) is 8.81%, illustrating an insufficient energy storage capacity. Furthermore, the energy shifting occurs in both several days scale and seasonal scale. This is obvious evidence for function of long duration energy storage (LDES) for the proposed coupled energy storage. Highlights: A green hydrogen-electric coupled energy storage system is proposed. The power-to-gas-to-power device is used to smooth long duration power fluctuation. The actual operation constraints of system are considered in performance evaluation. The multiple time-scale fluctuations in unbalance power can be well smoothed.